EVALUASI RASIONALITAS PENGGUNAAN OBAT DIABETES MELITUS TIPE II PADA PASIEN RAWAT JALAN DI PUSKESMAS PASIR SAKTI TAHUN 2019 - Dwi Aulia Ramdini; Lilik Koernia Wahidah; Dwi Atika (JFL : Jurnal Farmasi Lampung, 2020)
Abstract Diabetes mellitus is a metabolic disease characterized by hyperglycemia, due to abnormal insulin secretion, insulin action or both. Hyperglycemia is a condition in which blood glucose levels increase or exceed normal limits. This study aims to evaluate the treatment of type II diabetes mellitus in outpatients in Puskesmas Pasir Sakti. This research is a nonexperimental research with a descriptive design taken retrospectively. The sample in this study were all outpatients with a diagnosis of type II diabetes mellitus at Puskesmas Pasir Sakti 2019. The sampling technique used was Total sampling. The sample of this study is the medical record data of patients with type II diabetes mellitus in 2019 adjusted for inclusion criteria. Characteristics based on gender of patients with type II diabetes melitus there are 23 male patients that is 29% and 57 female patients that is 71 %. Characteristics based on the age of most patients in the Elderly (46-65 years) as many as 65 patients (81%). cases of type II diabetes mellitus patients without complications were 39 patients (49%) cases of type II diabetes mellitus patients with complications of 41 patients (51%). The results of the rationality of antidiabetic use in outpatients at the Puskesmas Pasir Sakti in 2019 According to PERKENI 2015 obtained the use of drugs based on the exact parameters indicated as much as 97.5%, the right drugs as much as 98.75%, the right dosage as much as 100%, the right way of administration as much as 100%, the exact time interval of 100%, and medication adherence of 100%. Treatment of type II diabetes melitus who received rational therapy was 96,25% while irational therapy is 3,75%. Keywords: Diabetes Mellitus, Evaluation, Medicine, Rationality.